Cobalt complexes of tetradentate, bipyridine-based macrocycles: their structures, properties and photocatalytic proton reduction. Issue 4 (24th December 2015) - Joliat, E.; Schnidrig, S.; Probst, B.; Bachmann, C.; Spingler, B.; Baldridge, K. K.; von Rohr, F.; Schilling, A.; Alberto, R.
Abstract : Photocatalytic proton reduction is demonstrated using a new type of cobalt catalyst with macrocyclic bis-bipyridine ligand frameworks, achieving turnover numbers up to 20 000 H2 /Co. Abstract : Complexes with purely pyridine-based macrocycles are rarely studied in photo(electro)catalysis. We synthesized and investigated macrocycles, in which two 2, 2′-bipyridine (bpy) units are linked twice by two cyano-methylene groups, to yield the basic tetradentate, bipyridine based ligand framework (pyr). The protons in the bridges were substituted to obtain derivatives with one (pyr-alk) or two (pyr-alk2 ) alkyl-chains, respectively. We present the crystal structures of the mono-pentylated and the cis -dibutylated ligands. The corresponding Co II complexes [Co II (OH2 )2 (pyr)], [Co II Br(HOMe)(pyr-bu)], [Co II Br2 ( cis -pyr-bu2 )] and [Co II Br2 ( trans -pyr-bu2 )] were prepared, their physico-chemical properties elucidated and their crystal structures determined. X-ray analyses revealed for the latter three complexes distorted octahedral coordination and a fairly planar Co II (pyr) macrocyclic scaffold. The axial bromides in [Co II Br(HOMe)(pyr-bu)], [Co II Br2 ( cis -pyr-bu2 )] and [Co II Br2 ( trans -pyr-bu2 )] are weakly bound and dissociate upon dissolution in water. While the alkylated complexes are paramagnetic and feature Co II d 7 high spin configurations, the unsubstituted complex [Co II (OH2 )2 (pyr)] displays a rare Co II low spin configuration. The electronic ground states of [Co II Br2 ( cis -pyr-bu2 )] and [Co II Br2 ( trans -pyr-bu2 )] are similar, as evident from the almost identical UV/vis spectra. Electrochemical analyses show redox-non-innocent ligand frameworks. All complexes are highly robust and efficient H + reducing catalysts. In the presence of [Ru(bpy)3 ]Cl2 as a photosensitizer and TCEP/NaHasc as a sacrificial electron donor and shuttle, turnover numbers (TONs, H2 /Co) up to 22 000 were achieved.